Fabrication and Characterization of Phthalic Acid Sensor for Detection of Lead (II) Ion - Oli, Hari Bhakta; Timilsina, Rajan; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2017)
available with full text